Does Size Matter? Evidence from Municipality Break-Ups - Gissur Ó Erlingsson; Jonas Klarin; Eva Maria Mörk (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Municipal break-ups are an understudied phenomenon despite the fact that such territorial reforms regularly take place across the globe. This paper estimates how seven voluntary splits of Swedish municipalities affected municipal current costs. To predict what would have happened had the break-ups not taken place, we apply the matrix completion method with nuclear norm minimization. Our results do not support the standard view, that smaller municipalities imply higher per capita costs. Instead, we find an intriguing heterogeneity: costs increase in some municipalities, are unaffected in others and decrease elsewhere. The findings point to the complex nature of territorial reforms, the difficulty in drawing general conclusions of such, and hence, the perils of expecting them to have uniform outcomes.
Keywords: H72; R12; R50; 330; territorial reforms; municipalities; matrix completion